Process parameters optimisation of mannanase production from Aspergillus niger FTCC 5003 using palm kernel cake as carbon source - Abd. Aziz, Suraini; Ong, Lisa Gaik Ai; Hassan, Mohd Ali; Abdul Karim, Mohamed Ismail (Academic Journals, 2008)
The aims of this study are to optimised the process parameters involved for submerged fermentation of mannanase by Aspergillus niger FTC5003 using palm kernel cake (PKC) as carbon source. The parameters investigated include temperature, agitation speed, inoculum size and PKC concentration. The submerged fermentation was carried out for 10 days by using palm kernel cake as the sole carbon source with the addition of nitrogen source. Palm kernel cake can be considered as a suitable carbon source for the enzyme production due to it mainly consist of mannan and galactomannan, which is hemicellulose. The mannanase enzyme production using the optimised fermentation condition, which was conducted at agitation speed of 200 rpm, temperature 35 Â°C, 1x104 spores mL-1 of inoculum size and 2% of palm kernel cake with productivity of 13.00 U/mL/day.